2011
DOI: 10.3201/eid1709.101948
|View full text |Cite
|
Sign up to set email alerts
|

Intrahousehold Transmission of Pandemic (H1N1) 2009 Virus, Victoria, Australia

Abstract: TOC Summary: Antiviral prophylaxis for quarantined contacts reduces secondary transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…Eleven studies recorded infection rates among household contacts that received antiviral prophylaxis, 19,23,24,27,28,32–34,36,44,46 but only one study reported the prophylaxis group to be more susceptible to pH1N1 (eFigure 3, http://links.lww.com). One study reported seasonal influenza vaccination history to have no effect on the SIR, 45 while three studies 24,30,35 reported elevated SIRs among people who had been vaccinated for seasonal influenza.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies recorded infection rates among household contacts that received antiviral prophylaxis, 19,23,24,27,28,32–34,36,44,46 but only one study reported the prophylaxis group to be more susceptible to pH1N1 (eFigure 3, http://links.lww.com). One study reported seasonal influenza vaccination history to have no effect on the SIR, 45 while three studies 24,30,35 reported elevated SIRs among people who had been vaccinated for seasonal influenza.…”
Section: Resultsmentioning
confidence: 99%
“…35,39 Among these, two studies with differing SIRs (estimated SIR PCR of 33% and 15%) were reported from Victoria, Australia at similar times. 29,44 The study with the larger SIR estimate recruited subjects by 31 August 2009 while the other ended on 3 June 2009; the proportion of child index cases (aged ≥5 years) was 86% in the study with SIR PCR =15%, compared with 37% in the other study. These are consistent with our findings from meta-regression (Table 2); the smaller SIR PCR in studies with a greater proportion of child index cases may also suggest case ascertainment bias.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 presents a flow chart of the selection process. The selected reports included outbreak analyses from the following countries: Australia [10], [12]–[14], Canada [15][18], Chile [19], China [20][22], Finland [23], France [24][27], Germany [28], [29],Hong Kong [30], [31], India [32], Japan [33][35], Kenya [36], Republic of Korea [37], Netherlands [7], New Zealand [38], Taiwan [39], United Kingdom (UK) [6], [40][45], and the United States (USA) [8], [9], [11], [38], [46][55]. Four reports provided analysis related to one outbreak in the USA [8], [9], [11], [51].…”
Section: Resultsmentioning
confidence: 99%
“…Household transmission of pandemic (H1N1) 2009 has the potential to trigger acommunity transmission and even a nationwide pandemic[7]. Previous studies have demonstrated that household transmission has accounted for up to 40% of all cases detected[12], and the occurrence of confirmed infection was >5% via close household contacts in Beijing[13]. …”
Section: Introductionmentioning
confidence: 99%